The Covid-19 pandemic spurred growth in automation: What does this mean for minority workers? - Kristen Broady; Darlene Booth Bell; Anthony Barr; Ryan Perry (Federal Reserve Bank of Chicago, 2023)
The Covid-19 pandemic has accelerated trends in automation as many employers seek to save on labor costs amid widespread illness, increased worker leverage, and market pressures to onshore supply chains. While existing research has explored how automation may displace nonspecialized jobs, there is typically less attention paid to how this displacement may interact with preexisting structural issues around racial inequality. This analysis updates that of a 2021 Brookings paper by the authors, finding that Black and Hispanic workers continue to be overrepresented in the 30 occupations with the highest estimated risk of automation and underrepresented in the 30 occupations with the lowest estimated risk of automation. The updated analysis also includes new attention to automation's impact on wage structures, consideration of the broader implications of automation for global economics, and a discussion of the potential interplay of automation with recent developments in artificial intelligence.
Keywords: D63; E24; I24; J21; J24; J31; O33; 330; Race; Automation; Covid-19